2010
DOI: 10.1210/en.2009-0929
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysteroid (17β) Dehydrogenase 12 Is Essential for Mouse Organogenesis and Embryonic Survival

Abstract: Hydroxysteroid (17beta) dehydrogenases (HSD17Bs) have a significant role in steroid metabolism by catalyzing the conversion between 17-keto and 17beta-hydroxysteroids. However, several studies in vitro have shown that some of these enzymes may also be involved in other metabolic pathways. Among these enzymes, HSD17B12 has been shown to be involved in both the biosynthesis of estradiol and the elongation of the essential very long fatty acids in vitro and in vivo. To investigate the function of mammalian HSD17B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…It has also been shown that silencing HSD17B12 expression with siRNA in an ovarian cancer cell line led to growth inhibition and increased apoptosis [14]. These data are in line with our data on HSD17B12 knockout mice, indicating an essential role for the enzyme in cell proliferation and differentiation during mouse development [15]. In all these studies, the growthpromoting effect of HSD17B12 was related to its role in AA production and not to the synthesis of estradiol.…”
supporting
confidence: 91%
“…It has also been shown that silencing HSD17B12 expression with siRNA in an ovarian cancer cell line led to growth inhibition and increased apoptosis [14]. These data are in line with our data on HSD17B12 knockout mice, indicating an essential role for the enzyme in cell proliferation and differentiation during mouse development [15]. In all these studies, the growthpromoting effect of HSD17B12 was related to its role in AA production and not to the synthesis of estradiol.…”
supporting
confidence: 91%
“…The yolk sac uses high-density lipoproteins (HDLs) and very-low-density lipoproteins (VLDL) as carriers to incorporate cholesterol from the maternal circulation and to transfer it to the embryonic side [16]. In turn, the interstitial lipid accumulation of cholesterol, a precursor molecule of many hormones like aldosterone, corticoids, androgens, strogens, and progesterone, may favor fluid infiltration and cell migration, proliferation, and differentiation during embryo development [19]. The ability to transport fat in the form of lipoprotein through the circulatory system by eukaryotes is one of their most significant functions right from the beginning of existence [20].…”
Section: Wound Repair Phenotypes: Gastrulation Revisitedmentioning
confidence: 99%
“…It is unknown if the inhibition of the respective enzymes in adults would also be lethal. Four other potential targets (Enolase 1 ( ENO1 ), Dihydrolipoamide Dehydrogenase ( DLD ), Glyceraldehyde-3-Phosphate Dehydrogenase ( GAPDH ) and Hydroxysteroid 17-Beta Dehydrogenase 12 ( HSD17B1 2)) are also essential in most of those cell lines and homozygous null mouse models for each of these genes die at the embryonic state [5962]. It has been shown that HSD17B12 knock down is linked to reduced lipid accumulation in adipocytes which would match the effect predicted by the network [63].…”
Section: Discussionmentioning
confidence: 99%